The Influence of Domestic Soybean Production, Consumption, Prices, and Exchange Rates on Soybean Imports in Indonesia - Pratiwi, Indah; Sutrisno, Joko; Antriyandarti, Ernoiz (Open Global Scientific Journal, 2025)
Background: Domestic soybean production that has not been able to meet national soybean needs is an implication of the decline in soybean harvested area in Indonesia. The opposite condition occurs at the level of demand for soybeans, which increases every year. The soybean import policy is an alternative step for government to overcome the gap between soybean production and consumption in Indonesia. Soybeans in this study are not separated from the type, namely with HS code 1201 (Soya beans, whether or not broken).Aims: This study aims to analyze the factors that influence soybean imports in Indonesia by using secondary data from 2001 to 2021. The research method used is descriptive quantitative.Methods: The analysis method used is OLS which is used to determine the regression equation so that the actual value can be know from each independent variable to the dependent variable.Results: The result of the study found that partially soybean production had no significant effect on soybean imports in Indonesia, soybean consumption had no significant effect on soybean imports in Indonesia, domestic soybeans prices had a significant effect on soybeans imports in Indonesia, the exchange rate had no significant effect on soybean imports in Indonesia, and simultaneously all free variable had a significant effect on soybean imports in Indonesia.